2002
DOI: 10.2136/sssaj2002.1200
|View full text |Cite
|
Sign up to set email alerts
|

A Point‐Source Method for Rapid Simultaneous Estimation of Soil Hydraulic and Chemical Transport Properties

Abstract: Hydraulic and chemical transport properties are needed for accurate prediction of water and chemical movement through the vadose zone. Field methods used to estimate such properties are often hampered by extensive labor and time constraints. One of the objectives of this study was to develop an experimental setup and a procedure for a point-source method that facilitates rapid and simultaneous measurements of soil hydraulic and chemical transport properties at multiple locations. Another objective was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A single applied tension yielded one set of values for the hydraulic conductivity, K, the total water content, θ, the water content of the immobile zone, θ im , and the mass transfer coefficient, α (Alletto et al, 2006), while several tracer infiltrations conducted at different tensions produced K, θ, θ im , and α, as near-saturated functions of the matric potential (Casey et al, 1998). Al-Jabri et al (2002) suggested a variant of this method for simultaneous measurement at multiple locations based on point-source dripper lines. They used the Wooding's (1968) analytical solution for estimating K and the capillary length, λ c , while MIM transport parameters were estimated according to Jaynes et al (1995).…”
Section: Scale II (Plot Field)mentioning
confidence: 99%
See 1 more Smart Citation
“…A single applied tension yielded one set of values for the hydraulic conductivity, K, the total water content, θ, the water content of the immobile zone, θ im , and the mass transfer coefficient, α (Alletto et al, 2006), while several tracer infiltrations conducted at different tensions produced K, θ, θ im , and α, as near-saturated functions of the matric potential (Casey et al, 1998). Al-Jabri et al (2002) suggested a variant of this method for simultaneous measurement at multiple locations based on point-source dripper lines. They used the Wooding's (1968) analytical solution for estimating K and the capillary length, λ c , while MIM transport parameters were estimated according to Jaynes et al (1995).…”
Section: Scale II (Plot Field)mentioning
confidence: 99%
“…They used the Wooding's (1968) analytical solution for estimating K and the capillary length, λ c , while MIM transport parameters were estimated according to Jaynes et al (1995). In an application with several dripping rates, the saturated hydraulic conductivity, K s , the ratio of the immobile and the saturated water content, θ im /θ s , and λ c were similar, while α was different compared to corresponding values derived using the disk infiltrometer (Al-Jabri et al, 2002). The dripper line method was further extended by the installation of a TDR probe beneath each infiltration spot to also measure solute breakthrough to yield the dispersion coefficient in the mobile region (Al-Jabri et al, 2006).…”
Section: Scale II (Plot Field)mentioning
confidence: 99%
“…For example, Brusseau et al (1994) used the gravimetrical mass balance method to measure the mobile water fraction and determined mass transfer coefficient in an aggregated soil in terms of Fick's law. In addition, these two parameters can be determined by experimental methods such as tension disk infiltrometer (Casey et al, 1999), point-source method (Al-Jabri et al, 2002), and time domain reflectometry (TDR) method (Lee et al, 2000). However, determining these two parameters independently is still a non-trivial task as they appear to be somewhat correlated, and the robust physical meaning of them needs further investigation (Griffioen et al, 1998;Maraqa, 2001).…”
Section: Mimmentioning
confidence: 99%
“…2.48) until the ponded zone approaches a constant circular or nearly circular area at some finite infiltration time. Once this saturated disk is formed, water continues spreading laterally on the soil surface forming an unsaturated zone (Yitayew et al 1998;Shani et al 1987;Al-Jabri et al 2002a). The unsaturated front is identified by the change of the soil color from wet to dry conditions.…”
Section: Dripper or Point-source Methodsmentioning
confidence: 99%